Inflammatory proteins in diabetic kidney disease—potential as biomarkers and therapeutic targets - Xiang, Angie S.; Ekinci, Elif I.; MacIsaac, Richard J. (Annals of Translational Medicine, 2019)
Diabetic kidney disease (DKD) affects approximately 40% of all people with diabetes, and is the leading cause of chronic kidney disease (CKD) and end-stage renal disease (ESRD) (1). With the increasing diabetes prevalence secondary to obesity, as well as improved survival among people with diabetes due to prevention and management of macrovascular complications, the morbidity and mortality form DKD can only be expected to increase in the future (2).